A CMOS power amplifier using an active balun as a driver stage to enhance its gain. (May 2017) - Sim, Yonghun; Park, Jonghoon; Yoo, Jinho; Lee, Changhyun; Park, Changkun
Abstract: In this study, we design a differential power amplifier using a 110-nm RF CMOS process. To improve amplifier gain, we propose an active balun as a driver stage of the power amplifier. The passive input balun is removed to minimize the substrate loss. In the proposed power amplifier structure, the active balun converts a single-ended signal into a differential signal and at the same time provides sufficient gain as the driver stage of the power stage. To verify the feasibility of the proposed power amplifier structure, we designed a typical and the proposed power amplifier using identical processes and with the same design parameters, except for the driver stage and the input transformer of the typical power amplifier. The measured improvement of the gain of the proposed power amplifier is approximately 4.2 dB compared to that of the typical power amplifier. From the measured results, we successfully prove the feasibility of the proposed power amplifier.